From HIV prevention to non-communicable disease health promotion efforts in sub-Saharan Africa: A Narrative Review. (1st July 2018) - Juma, Kenneth; Reid, Michael; Roy, Monika; Vorkoper, Susan; Temu, Tecla M.; Levitt, Naomi S.; Oladepo, Oladimeji; Zakus, David; Yonga, Gerald
Abstract : Objective: To synthesize published literature on noncommunicable disease (NCD) behavior change communication (BCC) interventions in sub-Saharan Africa (SSA) among persons living with HIV (PLHIV) and in the general population to inform efforts to adopt similar HIV and NCD BCC intervention activities. Methods: We conducted a literature review of NCD BCC interventions and included 20 SSA-based studies. Inclusion criteria entailed describing a BCC intervention targeting any four priority NCDs (cardiovascular disease, type 2 diabetes, cervical cancer, and depression) or both HIV and any of the NCDs. The RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) framework was used to assess potential public health impact of these studies. We also solicited expert opinions from 10 key informants on the topic of HIV/NCD health promotion in five SSA countries. Results: The BCC interventions reviewed targeted multiple parts of the HIV and NCD continuum at both individual and community levels. Various strategies (i.e. health education, social marketing, motivational interviewing, mobile health, and peer support) were employed. However, few studies addressed more than one dimension of the RE-AIM framework. Opinions solicited from the key informants supported the feasibility of integrating HIV and NCD BCC interventions in SSA potentially improving access, service provision and service demand, especially for marginalized and vulnerable populations. Conclusion: Although HIV/NCD integration can improve effectiveness of preventive services at individual and community levels, potential public health impact of such approaches remain unknown as reach, adoptability, and sustainability of both integrated and nonintegrated NCD BCC approaches published to date have not been well characterized.